Model checking dolev-yao multi-agent epistemic logic - Oliveira, Anna Carolina Carvalho Moreira de (2018)
We use the web for almost everything, including for actions that require high level of secrecy, for example, banking transactions. It make us think about the necessary security to keep this environment safe, that constantly suffers cyber attacks. For this reason, the study of cryptography is always in advance. Besides, It is important do not have vulnerability in security protocol too. In 1983, Dolev and Yao realize that in public key protocol, which is widely used even nowadays, a malicious user in a network can discover the contents of communications between other users simply by eavesdropping on the exchange of messages. Based on the model introduced in the Dolev and Yao’s article, we propose an epistemic logic extension to evaluate if a security protocol is safe. We transcripted this extension to strips language, where we can automatically test every possible intruder actions to discover contents of messages. And with this new notation we developed a model checker